Kemampuan CSR disclosure sebagai kosmetik earnings management - Hudaya, Robith; Sukma, Paradisa; Agustiningsih, Wulandari; Rahnaen, Feryadi (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to analyze the role of Corporate Social Responsibility (CSR) disclosure in moderating the effect of earnings management (EM) on firm market value. Method – The researcher employed a panel data regression method with a moderating variable approach. The sample consists of consumer cyclical companies listed on the Indonesia Stock Exchange (IDX) during the years 2022 and 2023. Findings – The results show that earnings management (EM) does not have a significant effect on firm market value. However, the level of CSR disclosure has a positive and significant impact on market value, indicating that investors respond positively to greater transparency in social and environmental reporting. Additionally, CSR disclosure is not proven to moderate the relationship between EM and firm market value. Implications – These findings have important implications for corporate management, regulators such as the Financial Services Authority (OJK), and the Indonesia Stock Exchange in formulating policies that promote social accountability and limit earnings management practices. Originality – The novelty of this study lies in the use of prior-year CSR data to capture the delayed effect of information on investor decision-making, as well as the application of a content analysis approach based on Global Reporting Initiative (GRI) items to enhance the validity of CSR disclosure measurement.